Marketplace colaborativo de venta de repuestos y accesorios para vehículos - Mister Fix - Rosario Palacios, Eduardo Carlo (2022)
Metropolitan Lima experiences constant vehicular congestion, investing inordinate time in moving the population to their destination, adding to this the mechanical failure of certain vehicles, causing chaos, stress and frustration in citizens. Drivers find it necessary to buy auto parts and spare parts, implying an additional effort to obtain them, since sometimes it is difficult to find the useful spare part for their vehicle, and there is a great diversity of prices that prevent knowing if they are buying the right spare part. or if the store has stock of the product. These stores sell conventionally, without an alternative space to the physical one, limiting their competitiveness. For this reason, the proposal of the Marketplace Mister Fix is made for the sale of vehicle parts and accessories, as a meeting point between suppliers and demanders of parts (B2C trade) managing to obtain the parts based on 3 pillars: Brand, price and location according to your need. It has tools that offer to improve the control of its stock, publish in an automated way and manage a "proactive sales system", knowing the life time of the product sold, managing to contact it before the spare part is at the end of its useful life. In addition, customers will be able to search for the products they need guided by variables that will help with the search of the platform's catalog, it has an electronic payment system and delivery according to the specified location. The aim is to minimize implementation costs in a platform for the sale of spare parts and auto parts, and according to sales forecasts, dynamic growth is expected according to demand as of the second year, being a great attraction for future investors. Finally, as results, it was obtained that the potential clients belong to the district of Miraflores (32%) and La Victoria (25%), from 30 to 40 years old (58%)